The Concept of People's Sharia Economy in The Perspective of Dignified Justice Theory: What and How? - Darmawangsa, Andi; Surani, Surani; Akil, M.; Ardi, Ardi; Putra, Aditya Halim Perdana Kusuma (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
Indonesia, as the world's largest Muslim-majority country, requires the development of an economic system that aligns with the principles of Islamic Sharia, one of which is through the concept of Sharia populist economy. This concept balances Sharia principles with the spirit of populism to achieve social justice and community welfare. The purpose of this research is to explore a deep understanding of the Sharia populist economy concept and how it can be integrated with principles of dignified justice. It also aims to analyze practical steps and strategies for implementing the Sharia populist economy concept in the Indonesian context, considering principles of dignified justice. This research employs normative legal research methods with a conceptual approach, using primary and secondary legal sources, data collection techniques through literature studies, and qualitative data analysis. The research findings reveal that the concept of Sharia populist economy is understood from the perspective of the theory of dignified justice as an effort to create an economic system that is fair, balanced, and prioritizes the welfare of all societal layers. This is achieved by integrating Islamic Sharia principles with the spirit of populism, involving active community participation in productive economic activities. This concept aims to create comprehensive justice, covering economic, spiritual, social, and environmental dimensions, ensuring that the entire society has equal opportunities to achieve well-being and dignity. Its implementation in Indonesia can be realized through a comprehensive approach, such as formulating supportive policies and regulations, developing adequate infrastructure, enhancing human resource capacities, encouraging active stakeholder participation, and the government's role in creating a conducive environment while maintaining principles of justice, balance, and welfare for all societal layers in line with the spirit of populism